2001
DOI: 10.1097/00001756-200111160-00030
|View full text |Cite
|
Sign up to set email alerts
|

Neural phenotype expression of cultured human cord blood cells in vitro

Abstract: Neural stem cells have been proposed as useful vectors for treating diseases in the CNS, but their utility is severely limited by lack of accessibility. Brain development is ongoing extensively in early postnatal life. However, it is unclear whether stem cells that differentiate into neurons exist in the blood during early postnatal life. We showed in this experiment that neural markers (NeuN, neurofilament, MAP2, GFAP) are expressed and long cytoplasmic processes are elaborated in the cultured human cord bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 23 publications
2
33
0
1
Order By: Relevance
“…Human umbilical cord blood (hUCB) (Prockop, 1997;Erices et al, 2000) has also been shown to contain large numbers of hematopoietic colony-forming cells (Nakahata and Ogawa, 1982). The mononuclear cells derived from hUCB cells, can be induced to express class III ␤-tubulin, glial fibrillary acidic protein (GFAP), GalC (an oligodendrocyte marker) (Galvin-Parton, 2003), and microtubule-associated protein 2 (MAP-2) (Ha et al, 2001). However, the complicated culturing conditions for in vitro expansion of MSCs, together with the required HLA (human histocompatibility leukocyte antigen) matching for hUCB transplantation between donor and recipient, may limit the clinical application of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Human umbilical cord blood (hUCB) (Prockop, 1997;Erices et al, 2000) has also been shown to contain large numbers of hematopoietic colony-forming cells (Nakahata and Ogawa, 1982). The mononuclear cells derived from hUCB cells, can be induced to express class III ␤-tubulin, glial fibrillary acidic protein (GFAP), GalC (an oligodendrocyte marker) (Galvin-Parton, 2003), and microtubule-associated protein 2 (MAP-2) (Ha et al, 2001). However, the complicated culturing conditions for in vitro expansion of MSCs, together with the required HLA (human histocompatibility leukocyte antigen) matching for hUCB transplantation between donor and recipient, may limit the clinical application of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of studies have shown that stem cells can promote angiogenesis under certain conditions, thus paving a new way for the treatment of limb ischemia (Sun et al, 2006b;Zhu et al, 2009;Chang et al, 2013). Umbilical cord mesenchymal stem cells have strong ability to proliferate and differentiate in vitro and have displayed good efficacy in the treatment of limb ischemia (Ha et al, 2001;Chen et al, 2009;Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although several reports revealed that HUCB cells expressed neural phenotypes both in vitro and in vivo (Garbuzova-Davis et al, 2003;Ha et al, 2001;Sanchez-Ramos et al, 2001;Zigova et al, 2002), few cord blood cells survive in the ischemic region compared to the number of infused cells Vendrame et al, 2004Vendrame et al, , 2005Willing et al, 2003aWilling et al, , 2003b). In addition, two studies using mannitol to permeate the blood brain barrier showed that the passage of growth factors into the brain following MCAO and neonatal hypoxic ischemia was more important than cell migration from the circulation following intravenous injection (Borlongan et al, 2004;Yasuhara et al, 2010).…”
Section: Probable Mechanisms Responsible For Neural Protectionmentioning
confidence: 99%